Kamëntzá indigenous education. Upbringing, thought, listening (2018)
This research article is based on the idea that school, as a Western apparatus, was imposed as a homogenizing strategy within the framework of a civilizational project in the Colombian territory during the nineteenth century and became a fundamental tool of coloniality when persecuting and eradicating cultural manifestations by indigenous peoples. Since there is no word such as education in Kamëntzá language, the people have established equivalences for its translation including, among others, education as upbringing, thought, experience, and ancestral knowledge. These are processes where the mother tongue, the preponderance of orality, the character acquired by collectiveness in the life within the community, the diverse spaces, and the value of adult people in the tradition as well as their preservation as people are cornerstones. However, many of these elements have been weakened, which threatens what is today known as indigenous’ own education and their cultural survival. Paradoxically, the research carried out finds that Western-like school has progressively turned into a space of language transmission to the new Kamëntzá generations and their own right it, thus creating spaces for meeting and safeguarding traditions as people.